Diseño de una colección de accesorios incorporando remanentes de cuero, denim y tejidos con técnicas de macramé para la empresa Texmodaec S.A.S - Aguilar Zapata, Gabriela Lizbeth (2025)
This study focused on the design of a collection that includes functional accessories made with remnants of leather, denim and fabrics using macramé techniques, with the purpose of promoting sustainability and preserving traditional craft techniques. For this purpose, a documentary and field research was carried out, which included the analysis of background information on sustainable fashion, the selection of materials by means of curatorial cards and experimentation with macramé techniques. This process identified optimal combinations of materials and methods to ensure the functionality and aesthetics of the products. The project contributed to the development of sustainable practices in the textile industry and to the reinforcement of cultural identity by integrating traditional elements into modern proposals. It also responded to the demands of a growing market that values sustainability and responsible procurement. In conclusion, the work demonstrated that it is possible to design sustainable accessories from remnants, contributing to the reduction of textile waste, the revaluation of artisanal techniques and the positioning of Texmodaec S.A.S. as a brand committed to the environment and fair trade.